Study on Strength Development of Concrete Using Rice Husk Ash, Quarry Dust and Polypropylene Fibres - Che Hamzah, Che Mohamad Redhwan; Abdul Ghani, Abdul Halim (Journal of Structural Monitoring and Built Environment, 2026)
River sand and cement consumption has increased because of Malaysia's rising demand for concrete production. This has a bad impact on the environment, such as a lot of mining and damage of river stability. This study aims to reduce these environmental issues by investigating the use of alternative materials in concrete mixtures. The study specifically investigates the use of rice husk ash (RHA) as a substitute for cement, quarry dust (QD) as a substitute for fine aggregate Polypropylene fibre (PPF) as an additive to enhance concrete properties. The objectives of this study are to evaluate the workability, density, water absorption, surface hardness and compressive strength of blended concrete mixes using RHA, QD and PPF. Additionally, the study aims to assess the strength performance of concrete with varying replacement levels of these materials and to determine the optimal blend of RHA, QD and PPF for the best concrete mix proportion. RHA replaces Ordinary Portland Cement (OPC) at varying percentage of 0%, 6%, 8%, 10% and 12%. QD will replacing fine aggregate at constant percentages of 20% and PPF will add with 1% of total concrete weight. All samples are expected to have a compressive strength of 30 MPa after 28 days. The Department of Environment's (DoE) concrete mix design method was used to prepare 36 samples and tests were performed to assess the samples' hardness, water absorption, compressive strength and workability. The  results show that while adding RHA, QD and PPF decreased the concrete's workability, higher percentages of QD and PPF replacement increased the concrete's compressive strength.